Victimization of mentally ill patients living in the community: is it a life-style issue? - Wood, Jane L. (Legal and criminological psychology, 2005)
Purpose. Although criminal victimization of mentally ill patients has been researched, what little work there is focuses on in-patient samples. This study aimed to compare crimes against mentally ill patients living in the community with crimes against students who have a high life-style risk of victimization. Methods. The samples were selected via community-based mental health services and a university population. A group of 40 mentally ill patients and 80 students reported experiences of victimization in the previous 12 months and attitudes towards the police. Results. Female mentally ill patients reported the highest victimization, but both male and female patients reported more victimization than did students. Mentally ill patients also held more negative opinions of the police. Conclusions. The results show that mentally ill patients experience more victimization when compared with the victimization experiences of a similar life-style risk group. Discussion focuses on the implications for mentally ill patients living in the community, the support networks available to them, and relations between the police and mentally ill patients.